Batak Toba Customary Inheritance Law from a Gender Justice Perspective - Abd Rohman (Jurnal Mengkaji Indonesia, 2025)
Abstract: The customary inheritance law of the Batak Toba adheres to a patrilineal system that prioritizes male descendants as the primary heirs, while female descendants have limited inheritance rights. This system is based on customary values that position men as the successors of lineage and guardians of family assets. However, the development of national law and the growing awareness of gender equality have driven changes in the inheritance practices of the Batak Toba, creating tensions between customary law and national law. Purpose: This study aims to analyze the inheritance system in Batak Toba customary law and explore the position of female descendants in obtaining their inheritance rights. It also seeks to identify the dynamics of changes in Batak Toba customary inheritance law in the context of gender justice. Design/Methodology/Approach: This study employs a normative juridical method with a statutory and conceptual approach. The primary legal materials used include relevant legislation and court decisions, while secondary legal materials consist of academic literature, journals, and other legal documents. Findings: The research findings indicate that the Batak Toba customary inheritance system is still dominated by patrilineal principles but has undergone shifts due to national legal intervention and social changes within the community. Supreme Court decisions have set precedents for recognizing the inheritance rights of female descendants, although gaps between customary law and national law persist in practice. Factors such as education, population mobility, and economic conditions also contribute to changes in the inheritance system. Originality/value: This study contributes to the understanding of the interaction between customary law and national law in inheritance matters and provides recommendations for creating a more inclusive and equitable legal system for women in the Batak Toba indigenous community.